Age-progressive interplay of HSP-proteostasis, ECM-cell junctions and biomechanics ensures C. elegans astroglial architecture - Coraggio, Francesca; Bhushan, Mahak; Roumeliotis, Spyridon; Caroti, Francesca; Bevilacqua, Carlo; Prevedel, Robert; Rapti, Georgia (Nature Communications, 2024)
Tissue integrity is sensitive to temperature, tension, age, and is sustained throughout life by adaptive cell-autonomous or extrinsic mechanisms. Safeguarding the remarkably-complex architectures of neurons and glia ensures age-dependent integrity of functional circuits. Here, we report mechanisms sustaining the integrity of C. elegans CEPsh astrocyte-like glia. We combine large-scale genetics with manipulation of genes, cells, and their environment, quantitative imaging of cellular/ subcellular features, tissue material properties and extracellular matrix (ECM). We identify mutants with age-progressive, environment-dependent defects in glial architecture, consequent disruption of neuronal architecture, and abnormal aging. Functional loss of epithelial Hsp70/Hsc70-cochaperone BAG2 causes ECM disruption, altered tissue biomechanics, and hypersensitivity of glia to environmental temperature and mechanics. Glial-cell junctions ensure epithelia-ECM-CEPsh glia association. Modifying glial junctions or ECM mechanics safeguards glial integrity against disrupted BAG2-proteostasis. Overall, we present a finely-regulated interplay of proteostasis-ECM and cell junctions with conserved components that ensures age-progressive robustness of glial architecture.
Online veröffentlicht: 3. April 2024
Gesehen am 06.09.2024